2022
DOI: 10.21927/ijnd.2021.9(1).19-26
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of online food ordering is not risk factor of central obesity in women aged 20 - 49 years

Abstract: <p><strong>ABSTRAK </strong></p><p><strong>Latar Belakang:</strong> Obesitas adalah masalah kesehatan dunia dengan prevalensi terus meningkat dari tahun ke tahun. Wanita secara umum lebih banyak mengalami masalah berat badan dibandingkan dengan laki-laki. Perkembangan teknologi berpengaruh terhadap gaya hidup sedentari yang menyebabkan kenaikan berat badan. Wanita paling sering melakukan pemesanan makanan online dibandingkan laki-laki.</p><p><strong>T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…These findings corroborated those of a study done at Taif University in the Kingdom of Saudi Arabia (Hamam et al, 2017) [24], which concluded there is no meaningful correlation between socio-demographic factors and WC (P value >0.05). Also, these results agreed with the study findings [25] revealing that there was no significant association between the socio-demographic characteristics and abdominal obesity (P. value >0.05).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings corroborated those of a study done at Taif University in the Kingdom of Saudi Arabia (Hamam et al, 2017) [24], which concluded there is no meaningful correlation between socio-demographic factors and WC (P value >0.05). Also, these results agreed with the study findings [25] revealing that there was no significant association between the socio-demographic characteristics and abdominal obesity (P. value >0.05).…”
Section: Discussionsupporting
confidence: 91%
“…According to the IRAS Family Study (Insulin Resistance Atherosclerosis Study), studies in people who exercised compared to those who exercised infrequently or not at all discovered that there was a drop in adipose, visceral, and subcutaneous tissues. As for the number of meals in our research, the current study reveals that increasing the frequency of meals (>3 times) increases central obesity, these results agreed with the study findings done by [25]. This may be explained according to Malik et al, (2013) [29], who indicated that when a person's caloric intake exceeds their energy expenditure, weight gain results from a positive energy balance.…”
Section: Discussionsupporting
confidence: 90%
“…The bivariate and multivariate analysis results showed no significant association between the frequency of online food ordering and central obesity. The findings of this study support the results of a study conducted on a sample of women aged 20-49 years in Sleman Regency 36 . This study did not examine what types of food the sample ordered, so the energy content of the food ordered could not be known.…”
Section: Copyright ©2023 Faculty Of Public Health Universitas Airlanggasupporting
confidence: 88%
“…Factors that can increase the risk of obesity include genetics, diet, drugs, hormonal, and physical activity 35 . The results of a similar study stated that the frequency of ordering through food delivery applications ≥ 3 times a week was not a risk factor for central obesity 29 . The results of research conducted on Siliwangi University students stated that energy and protein intake, as well as physical activity, are risk factors for obesity 36 .…”
Section: Relationship Between Frequency Of App Use and Obesity Riskmentioning
confidence: 91%
“…Students who tend to choose fast food as the chosen food have various reasons such as being lazy to wait a long time, easier to get, cheaper, considered tastier, and carried away by the influence of friends 28 . Research conducted in 2022 also shows that fried chicken is the most frequently ordered food through food delivery applications 29 . The relationship between strong influence from friends can be related to the frequency of fast food consumption 30 .…”
Section: Types Of Food/drink Purchased Through Food Delivery Applicat...mentioning
confidence: 99%